2009
DOI: 10.1021/ic8015657
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Preference of Rhodamine-Thiospirolactams for Mercury(II) in Aqueous Solution

Abstract: This work presents the design, syntheses, photophysical properties and Hg(2+)-binding of the red-emitting rhodamine derivatives RS1, RS2, and RS3 with different coordination ability and different spatial effects that derived from rhodamine thiohydrazone chromophores and respective carboxaldehydes (benzaldehyde, pyridine-2-carboxaldehyde, ferrocenecarboxaldehyde). Chemosensors RS2 and RS3 afford turn-on fluorescence enhancement and display high brightness in water with the EC(50) for Hg(2+) of 0.5 ppb. The fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(41 citation statements)
references
References 72 publications
0
41
0
Order By: Relevance
“…Rhodamine B, rhodamine 6G, maleic anhydride (MAH) and succinic anhydride (SAH) were purchased from Sigma-Aldrich Trading Co. Ltd. (Shanghai, China); Hydrazine hydrate, thionyl chloride and dimethyl sulfoxide (DMSO) were purchased from Sinopharm Chemical Reagent Co. Ltd. (Shanghai, China) and used without further purification; Anhydrous methanol and ethanol, acetic ether, dichloromethane, petroleum ether, N,Ndimethylformamide (DMF) and pyridine were obtained from commercial suppliers. Rhodamine B hydrazide (RBH) and rhodamine 6G hydrazide (R6GH) were prepared according to the literature method [32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…Rhodamine B, rhodamine 6G, maleic anhydride (MAH) and succinic anhydride (SAH) were purchased from Sigma-Aldrich Trading Co. Ltd. (Shanghai, China); Hydrazine hydrate, thionyl chloride and dimethyl sulfoxide (DMSO) were purchased from Sinopharm Chemical Reagent Co. Ltd. (Shanghai, China) and used without further purification; Anhydrous methanol and ethanol, acetic ether, dichloromethane, petroleum ether, N,Ndimethylformamide (DMF) and pyridine were obtained from commercial suppliers. Rhodamine B hydrazide (RBH) and rhodamine 6G hydrazide (R6GH) were prepared according to the literature method [32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of rhodamine skeletal to construct probes of the ''off-on'' type was a reliable method due to the well-known spirolactam (fluorescence ''off'') to ring-opened amide (fluorescence ''on'') equilibrium of rhodamine derivatives [17,[26][27][28][29][30][31][32][33][34]. The spirolactam moiety of rhodamine skeletal served as a signal switcher, which was observed to turn on when the cation was bound.…”
Section: Absorption Spectroscopic Studiesmentioning
confidence: 99%
“…Particularly, the lack of additional binding sites, except for these two atoms, made the probe show no or little coordination to any other metal ions but allow only the most preferred cupric ion to bind to the chelating unit. Recently, the spirolactam forms for the derivatives of rhodamine B or G skeletals have been utilized for the detection of other metal ions such as Hg 2 + [25][26][27][28], Cu 2 + [29], Fe 3 + [30], Cr 3 + [31,32], Pb 2 + [33,34], etc. in aqueous solutions via ring-opening processes of spirolactam amides or hydrazides.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few papers were reported for the determination of Hg(II) in the range of microgram to nanogram level by fluorimetric method [3,[16][17][18][19][20][21][22][23][24]. It has been reported that, triazinethione derivative [16], rhodamine-hydrazone derivative [17], rhodamine-thiospirolactams [18], rhodamine 6G-derivative [19], rhodamine B selenolactone [20], p-dimethylaminobenzaldehyde thiosemicarbazone [21] and 6-mercaptopurine [22], [E-4,4 0 -di(N-(2-pyridyl)amino) stilbene] [23], metal nanoparticles [24][25][26] can be used for the determination.…”
Section: Introductionmentioning
confidence: 99%